Comparisons between high power fiber systems in the presence of radiation induced photodarkening. (1st May 2022) - Tao, Mengmeng; Chen, Hongwei; Feng, Guobin; Wang, Lijun; Ye, Jingfeng; Wang, Yamin; Ye, Xisheng; Chen, Weibiao
Abstract: Performance of high power fiber lasers and amplifiers with different pump sources are evaluated in the presence of radiation induced photodarkening in post-irradiated active fibers. Evolutions of output power and thermal mode instability threshold under different radiation doses are examined and analyzed. Severe degradation in both output power and thermal mode instability threshold is recorded for high power fiber systems with their active fibers exposed to radiations. Comparisons show that, amplifiers present a relatively better performance than lasers in adverse environments. Besides, 976 nm pump source is more favorable for high power laser sources in radioactive applications, even though 915 nm pump ensures a much lower temperature profile inside the active fiber.